Webinar technology-based science article writing training - Permana, Septian Aji; Hartanto, Supri; Lia, Ayuningrum; Magiman, Muhamad Maulana (IOP Publishing, 2021)
The purpose of this Community Service is to equip doctors in the field of writing scientific articles for promotion. The results of medical research in the form of research in the health environment can be used as a scientific article to be published in national and international journals. The method used in assisting the writing of scientific articles based on health research is by the direct practice of writing articles and their implementation submitted in journals. The method used in this research-based article writing assistance is by the direct practice of writing and its implementation in submitting articles to journals through Webinars. The results of this article writing assistance are felt to be very beneficial for doctors in the Bantul Health Service area, Yogyakarta. Through two days of training, doctors can write health research-based articles. Doctors can also easily be promoted when the articles are published in proceedings or scientific journals. Through this article training, it can increase the motivation of doctors in improving their functional positions and support better doctor interactions, so that the future hope is to improve the performance of doctors.